Injury to infrapatellar branch of saphenous nerve in anterior cruciate ligament reconstruction using vertical skin incision for hamstring harvesting: risk factors and the influence of treatment outcome - Ochiai, Satoshi (J Orthop Surg Res, 2017)
BACKGROUND: Injury to the infrapatellar branch of the saphenous nerve (IPBSN) is a high-frequency complication in anterior cruciate ligament (ACL) reconstruction. We analyzed the risk factor of IPBSN injury in ACL reconstruction. Moreover, we investigated the influence on treatment outcome by this complication. METHODS: One hundred twenty-three patients who underwent ACL reconstruction using semitendinosus tendon graft were studied. Gender, age, BMI, and additional use of gracilis tendon were recorded. Treatment outcome was assessed by Lysholm score, visual analog scale (VAS) pain score, anterior knee pain, knee range of motion (ROM), and the patient-based SF-36. Patients who developed sensory disturbance at 24 months after reconstruction were compared with those without sensory disturbance. RESULTS: Twenty-six of 123 patients (21.1%) developed postoperative sensory disturbance caused by IPBSN injury. Baseline parameters were not significantly different compared to those in the non-sensory disturbance group. In the sensory disturbance group, treatment outcome evaluated at 24 months post-reconstruction showed Lysholm score of 94.1, VAS of 9.8 mm, anterior knee pain in 7.7%, and limitation of knee extension of 5° in 7.7%. SF-36 scores in all subscales were above the mean national standard scores. Treatment outcome parameters were also not significantly different compared to those in the non-sensory disturbance group, and none of the patients had serious impairment of knee function and activities of daily living. CONCLUSION: Injury to IPBSN in ACL reconstruction was not related to age, gender, and physique, and injury frequency did not increase. Evaluation of postoperative treatment outcome showed that IPBSN injury was not related to anterior knee pain or knee ROM limitation, and patients’ subjective evaluation confirmed no serious impact on physical and mental health.